Cold-Sprayed Aluminum-Silica Composite Coatings Enhance Antiwear/Anticorrosion Performances of AZ31 Magnesium Alloy - Lijia Fang; Yuting Xu; Li Gao; Xinkun Suo; Jianguo Gong; Hua Li (Advances in Materials Science and Engineering)
Extensive efforts devoted in recent years to booming structural applications of lightweight magnesium alloys are usually undermined by their insufficient surface properties. Surface modification is therefore necessarily required in most cases for enhanced surface integrity of the alloys. Here, we report construction of aluminum-silica protective layers by cold spray on AZ31 magnesium alloys, and the effect of the silica additives on microstructure and mechanical properties of the coatings was examined. The ceramic particles were dispersed evenly in the coatings, and increased silica content gives rise to enhanced adhesion, antiwear performances, and microhardness of the coatings. The even distribution of silica in the coatings altered the wear regimes from adhesive to abrasive wear. The cold spray fabrication of the aluminum-silica protective coatings would facilitate structural applications of the magnesium alloys.